Analisis Karakteristik Berita Hoaks di Media Online Voa-Islam.com - Nur Faisah (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2019)
This study aims to determine the characteristics of the Hoaks news on Voa-Islam.com media and to find out the differences in the characteristics of Hoaks news and not the Hoaks on Voa-Islam.com media. This type of research uses descriptive methods with qualitative analysis. Data sources use Primary Data and Secondary Data. The data collection technique used here is to document the Voa-Islam.com news, by studying, exploring, and citing theories. The data analysis technique used is gathering news, analyzing news, classifying news, analyzing news, and determining Hoak sand not Hoaks for their characteristics. The results showed that the characteristics of the Hoaks news in theVoa-Islamic media were not writing the date of the incident, the location of the incident was unclear, the content was strange and straight forward to corner certain parties, the news was not balanced, conveyed facts and biased considerations, the language and sentence structure used were some what ambiguous and unrelated to each other, using emotional and provocative language.